INDEKS KEBAPUHAN DAN INDEKS KONFORMASI TUBUH KAMBING SAPERA JANTAN DENGAN PEMBERIAN PAKAN BERBASIS INDIGOFERA SP. - Ramadhan, Divan Janatra; Setyaningrum, Agustinah; Priyono, Agus (ANGON: Journal of Animal Science and Technology, 2022)
Background. Research entitled "Plumpness Index and Body Conformation Index of Male Saperan Goats on Indigofera sp. Based Feeding." has been held from May 5, 2021 until July 11, 2021 at the Experimental Farm, Faculty of Animal Science, Jenderal Soedirman University. The purpose of the study was examine the benefits of Indigofera sp. on the plumpness index and body conformation index as a substitute for commercial concentrate at male Sapera goats. Materials and methods. Materials used were 18 male Sapera goats, aged 8-12 months and have weight of 18-25 kg, fresh Indigofera sp., dried Indigofera sp., commercial concentrate, field grass, water. The goat pen that used was an individual type stage cage along with feeding trough and drinking bucket, rulers, metlines, pen, book and scales. The research design used was a completely randomized design (CRD) which consisted of 3 treatments with 6 replications, so there were 18 experimental units. The treatments were P0 (50% field grass + 50% commercial concentrate), P1 (50% field grass + 20% commercial concentrate + 30% Indigofera sp. fresh), P2 (50% field grass + 20% commercial concentrate + 30 % dried Indigofera sp.). The results of the average plumpness index of P0 were (0.91 ± 0.10), P1 were (0.94 ± 0.05), P2 were (0.98 ± 0.06). The results of the average body conformation index of P0 were (0.28 ± 0.008), P1 were (0.30 ± 0.006), P2 were (0.28 ± 0.004). Results. The results of the analysis of variance showed that Indigofera sp. had no significant effect (P>0.05) on the plumpness index but had a significant effect (P<0.01) on body conformation index. HSD test results showed P1 (Indigofera sp. fresh) as the best for the body conformation index of male Sapera goats. Conclusion. In conclusion, Indigofera sp. feeding does not reduce the productivity of male Sapera goats but it can be used as a substitute for commercial concentrates up to 60% of commercial concentrates.